La protección del personal sanitario y las unidades sanitarias bajo el Derecho Internacional Humanitario: una aproximación a partir de los ataques en Gaza - Vergara Lamadrid, Ana (2024)
The aim of this article is to introduce the specific regulation on the special protection that International Humanitarian Law provides to medical personnel and medical units in the context of armed conflicts. What is more, it seeks to present the current panorama in relation to compliance with this special protection in different conflict zones such as Syria and Afghanistan, as well as the case law development in the International Tribunal for the Former Yugoslavia and the International Criminal Court. Finally, the article presents a brief analysis of the situation in the Gaza Strip, especially in relation to the attack on Al Shifa Hospital.